The impact that a Nelson Mandela Bay reform program has on the life improvement of previously incarcerated adults - George, Demi (The IIE, 2020)
In South Africa, prison conditions are significantly different in comparison to the country’s western counterparts. Changing the way prisons operate would be exceptionally challenging for the country. Therefore, one needs to consider the nonprofit organisations that are available for prisoners while they are serving their sentence, but especially after they have served their sentence. This study has made use of the interpretivist research paradigm to answer the research problem posed. By making use of principles such as sense of belonging, rehabilitation and reform, and motivation and life satisfaction. The researcher was able to use this as a theoretical foundation for the data interpretation of the study. The study made use of questionnaires to draw information from four qualified social workers who facilitate the NMB NICRO prison reform programs, which is a non-profit organization which deals specifically with the rehabilitation and reform of previously incarcerated adults. The findings of the study show that through life skills programs and constant intervention, rehabilitation and reform of offenders can be achieved.
Keywords: Reform programs; Previously incarcerated adults; Nelson Mandela Bay